Training load and acute performance decrement in soccer - Montini, M.; Scotto di Palumbo, A.; Cotugno, V.; Augusto, M.; Sacchetti, M.; Nicolò, A. (International Journal of Sports Physiology and Performance, 2025)
Purpose: We investigated the association between training metrics commonly used in soccer and the acute performance decrement (APD) observed after 3 training sessions differing in exercise intensity and duration.